In with the Old, in with the New: The Promiscuity of the Duplication Process Engenders Diverse Pathways for Novel Gene Creation. (13th September 2012) - Katju, Vaishali
Abstract : The gene duplication process has exhibited far greater promiscuity in the creation of paralogs with novel exon-intron structures than anticipated even by Ohno. In this paper I explore the history of the field, from the neo-Darwinian synthesis through Ohno's formulation of the canonical model for the evolution of gene duplicates and culminating in the present genomic era. I delineate the major tenets of Ohno's model and discuss its failure to encapsulate the full complexity of the duplication process as revealed in the era of genomics. I discuss the diverse classes of paralogs originating from both DNA- and RNA-mediated duplication events and their evolutionary potential for assuming radically altered functions, as well as the degree to which they can function unconstrained from the pressure of gene conversion. Lastly, I explore theoretical population-genetic considerations of how the effective population size (N e ) of a species may influence the probability of emergence of genes with radically altered functions.